Effect of house prices, product quality on customer loyalty through customer satisfaction in housing Permata Royal Garden Malang - Setiawan, Hadi; Firdiansjah, Achmad; Darsono, Junianto Tjahjo (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study aims to analyze the influence of price and product quality to customer loyalty; analyze the influence of customer satisfaction on customer loyalty and analyze the influence of price, product quality to customer loyalty through customer satisfaction at Permata Housing Royal Garden Malang. This research is included in the explanatory research category, i.e to find out whether an associate variable or not with other variables, or whether a variabel is caused or influenced or not by other variables. The population in this study is all users of home buyers and who occupy the house in Permata Royal Garden Malang, amounting to 119 people. The sampling technique used is to use the census, which takes the entire data from users who buy and occupy the house in Permata Housing Royal Garden. After the research, the data collected were 87 respondents, because 32 home users are empty and not occupied. The analysis technique uses path analysis.Price and quality of the product can increase customer satisfaction, it indicates that customer satisfaction will be created with reasonable price, affordable, isesuai with its quality, competing price, price discount and good quality of production. In this case if the price of a house in Permata Royal Garden is reasonable and affordable, in accordance with its quality, competitive prices, discounted price and good product qualityof home buyers satisfied The price and quality of products that match the expectations of consumers will give rise to satisfaction for consumers and build customer loyalty levels. The price of the house and the qualification of a good product of the Royal Garden Gem can provoke customer loyalty to say positive things to others. Consumer satisfaction can increase customer loyalty. Level consumers' feelings after comparison of what they accept and their expectations that customer satisfaction will lead to customer loyalty. Customer satisfaction is able to mediate price effects, product quality to customer loyalty, which means that the price, quality of home products in the Courtesy of Royal Garden well-matched and goodwill can increase customer loyalty, when the customer feels satisfied with the home purchased at Permata Royal Garden.